BUNYI SERTAAN PADA PELAFALAN PENYANYI YURA YUNITA: PEMANFAATAN KAJIAN FONETIK SEBAGAI BAHAN AJAR MATA KULIAH FONOLOGI - Frilia Shantika Regina (STKIP Siliwangi, 2020)
One type of phonetic study is the accompanying sound. The sound of inclusion indaily life is often not recognized. This is becouse the accompanying sound is produced accidentally by the speaker. Assessment of speech sound can improve the ability of students to listen and identify one type of phonetic study, teh sound of inclusion. The research method used is a qualitative research method with descriptive analysis research type. The data in this study were divided into primary data in the from of songs sung by singer Yura Yunita and secondary data in the from of books, journals, and articles. Data analysis is done by collecting all the notes in the fiels, then reducing the data in the form of sound, after that present it into a pattern that is formed, to produce conclusions. Based on the results of an analysis of two songs entitled “Malam Sunyi” and “ Harus Bahagia” found thirtteen accompanying sounds. The thirteen accompanying sounds are included in teh types of sounds including labisation, palatalization, retroflexion, glottalization, aspiration, and nasalization. Thus, teh song spoken by Yura Yunita can be used as an alternative teaching materials for phonology courses, especially in the accompanying soun materials.